Reforming Indonesian Criminal Justice: Integrating Recidivism Risk Assessment for Fair and Effective Sentencing - Zahra, Salma; Azizan, Akmal; Sophia, Sally; Perai, Nurajam (Jurnal Hukum dan Peradilan, 2024)
The major goal of this study is to develop a contextually appropriate and nuanced framework for incorporating recidivism risk indicators into sentencing recommendations in Indonesia. This research seeks to bridge the gap between global best practices and Indonesia's unique sociocultural setting by performing a deep investigation of the cultural and legal intricacies particular to Indonesia and comparing worldwide methods. The study also highlights the significance of pre-sentence investigations in obtaining a complete picture of offenders' histories and habits and so shaping sentencing choices. The study's approach includes a comprehensive review of relevant Indonesian literature, laws, and case law. The methods include a comparative study that draws parallels between domestic and international norms in places like the USA, UK, DE, and FR. The research recommends risk factor criteria that are particular to Indonesia, taking into account the country's culture and legal system. Juvenile imprisonment, elements in sexual crimes against minors based on age, and complex conceptions of interpersonal connections are all examples of these aspects. The study supports using these culturally sensitive characteristics into sentencing standards to improve the judicial system in Indonesia. The report also emphasizes the significance of pre-sentence investigations in providing judges with comprehensive data for making fair and effective sentences. This study promotes continuing discussion and growth within Indonesia's criminal justice system by filling in knowledge gaps and providing concrete recommendations for better incorporating recidivism risk variables into sentence guidelines.